A pilot biomechanical study comparing a novel, intramedullary Nail/Plate construct to standard Dual-Plate fixation of intra-articular C2.3 distal humerus fractures. Issue 10 (October 2020) - Shah, Neil V.; Hayes, Westley T.; Wang, Hanbin; Hordines, John C.; Karakostas, Jonathan E.; Paxinos, Odysseas; Koehler, Steven M.
Highlights: We propose a combining absolute and relative bony stability with a novel plate-nail construct for distal humerus fractures. The nail/plate construct was non-inferior to dual-plate fixation with regards to stiffness and load to failure. Revision recommendation rate by consultant hand/upper extremity surgeons reviewing failure methods and radiographs was comparable between constructs. The Nail/Plate construct warrants further evaluation as an alternative to dual-plate fixation method for distal humerus fractures. Abstract: Background: The gold-standard treatment for intra-articular distal humerus fractures (DHFs) is dual-plate/dual-column fixation, though optimal orientation is not yet established. With a superior method not yet identified, we propose a load-sharing construct, combining absolute stability (extramedullary plate fixation) for distal articular fragments and relative stability (load-sharing intramedullary nail) for the metaphyseal segment. The purpose of this pilot study was to evaluate the biomechanical performance of a novel implant compared to orthogonal dual-plating. Materials and methods: Ten fresh-frozen matched-pairs of human cadaveric upper extremities with no prior elbow pathology/surgery were used. Pairs were randomized into two groups: Dual-Plate (medial and posterolateral) or novel Nail/Plate (cross-locked medial nail and posterolateral plate). AO/ASIF type 13-C2.3 multifragmentary fractures with simulated metaphyseal comminution. Biomechanical testing included stiffness (MPa) and load to failure (Newtons) in axial (100 cycles at 3 Hz at 20 N increments from 20 to 100 N) and coronal (varus/valgus; 4, 000 cycles from 50N-100 N at 3 Hz) planes. Failed specimens were not analyzed and mechanisms were identified. For all failures, mechanisms were identified and reviewed by three consultant surgeons for revision vs. immobilization, to attempt to recreate a real-world scenario. All outcomes were compared between groups. Results: During stiffness testing, zero Nail/Plate specimens failed, but two (20%) Dual-Plate specimens failed (mechanisms: fracture diastasis; bone collapse and intussusception into osteotomy, yielding articular congruency loss). For remaining samples, Nail/Plate ( n  = 10) coronal (varus/valgus) stiffness was comparable to Dual-Plate ( n  = 8) constructs (41.5 vs. 39.0 MPa, p  = 0.440). Remaining Dual-Plate constructs had greater axial overall stiffness than Nail/Plate (118.3 ± 48.3 vs. 95.6 ± 34.7 MPa, p  = 0.020). Failure loads were comparable between Nail/Plate and Dual-Plate constructs (1, 327.8 vs. 1, 032.4 N, p  = 0.170). Individual nail yield strength ranged from 1, 101.1–1, 124.4 N ( n  = 2). In review of all failures, the most common overall mechanism was fracture/osteotomy site posterolateral plate bending. Revision recommendation rate was comparable between constructs (Nail/Plate, 22.2% vs. Dual-Plate, 44.4%, p >0.05). Conclusions: The novel Nail/Plate construct demonstrated non-inferior coronal (varus/valgus) stiffness, despite producing lower axial stiffness than orthogonal dual-plating, potentially due to the load-sharing cross-locked design. Considering comparable biomechanical performance, with no failures and comparable recommendations for revision, this novel construct warrants further evaluation as an alternative to the gold-standard, dual-plate fixation method for intra-articular distal humerus fractures. Level of evidence: N/A